2010
DOI: 10.1093/ejechocard/jeq018
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular pacing increases tricuspid regurgitation grade regardless of the mechanical interference to the valve by the electrode

Abstract: Active RV pacing is associated with a significant increase in TR grade. This effect is not induced by acute changes in the RV area and is unrelated to an interference with leaflet closure by the electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 13 publications
3
52
0
6
Order By: Relevance
“…Однако невозможно обсуждать данную проблему, пер-воначально не рассмотрев возможные механиз-мы (см. рисунок) и предикторы ее возникнове-ния [6,[23][24][25][26].…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Однако невозможно обсуждать данную проблему, пер-воначально не рассмотрев возможные механиз-мы (см. рисунок) и предикторы ее возникнове-ния [6,[23][24][25][26].…”
Section: Discussionunclassified
“…В 44% случа-ев (n = 18) определялась лишь легкая степень, недостаточность клапана больших градаций не выявлена. Однако даже выраженная ТР может быть пропущена из-за акустических теней от электродов или неоптимальной визуализации струи регургитации, что является определенным ограничением в диагностике [6].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…14,15) In addition, several studies have demonstrated that a right ventricular (RV) lead induced tricuspid regurgitation (TR). [16][17][18][19] The mechanisms whereby a RV lead induces TR are not fully elucidated. Although some investigators have attributed TR to active RV pacing causing valve malfunction through RV mechanical dyssynchrony, 16) most have suggested mechanical interference of the lead with the valve leaflets leading to incomplete valve closure.…”
Section: Discussionmentioning
confidence: 99%